Mouvements Armés, Déplacements Forcés Et Enseignement/Apprentissage Dans Les Établissements Scolaires Des Pays Aux Abords Du Lac Tchad - Alhadji, Mahamat (European Scientific Journal, ESJ, 2018)
In a context marked by fear and instability of the populations, this article describes the influence of the armed movements as well as forced displacements caused by the exactions of the Boko Haram sect on the teaching and learning in schools of refugee children in countries bordering Lake Chad. The study conducted in the Minawao External Refugee Camp and the Zamani IDP site in the Far North Region of Cameroon reveals that crisis situations have a significant impact on the teaching/learning of refugee children. This influence can be seen through the learning conditions and difficult school pathways of refugee students in the Minawao and Zamai camps. In addition, the attitudes and practices of teachers, the quality of supervision and effective monitoring of students by their parents appear as other real niches that should not be lost sight of. Thus, it would be important for all refugee students arriving in camps to benefit from continuity of appropriate school services in order to match the teaching and learning of refugee children with the education systems of Lake Chad countries.